Evaluation of Protective Effect of Aegle Marmelos Fruit (BAEL) On Diclofenac Sodium Induce Gastrointestinal Toxicity - Kushawaha, Harkesh; Singhai, Akhlesh Kumar (Journal of Neonatal Surgery, 2025)
Aegle marmelos, a native plant of India, is a significant medicinal plant with ethnomedicinal applications in traditional and folk systems. It is grown as a temple garden plant and its leaves are used to pray Lord Shiva. The plant is considered sacred by Hindus and its fruits are used in traditional medicine and as food. A study aimed to assess the protective effect of Aegle marmelos fruit on gastrointestinal toxicity in mice. The study investigated the phytochemical constituents and medicinal value of Aegle marmelos fruit extracts, conducting GC-MS chromatography and analyzing antioxidant, TPC, TFC, toxicity, and anti-gastrointestinal toxicity properties of these fruit extracts. Results showed that AEAM and MEAM were safe up to a dose of 2000 mg/kg body weight without causing drug-related toxicity, mortality, abnormal clinical signs, remarkable body weight, or gross pathological changes. AEAM and MEAM significantly influenced the volume of gastric juice, pH, and free acidity of gastric juice. The administration of Omeprazole and AEAM and MEAM significantly influenced oxidative stress parameters in mice. The study also revealed that diclofenac administration caused significant alterations in the EC group compared to normal rats. Pretreatment with AEAM and MEAM attenuated the damage due to diclofenac administration, with lesser degree of tissue necrosis and hemorrhage. In conclusion, AEAM and MEAM of Aegle marmelos fruits proved to be a Gastroprotective agent against Diclofenac-induced GIT toxicity.